2016
DOI: 10.3758/s13415-015-0400-5
|View full text |Cite
|
Sign up to set email alerts
|

The time course of visual influences in letter recognition

Abstract: This study builds on a specific characteristic of letters of the Roman alphabet-namely, that each letter name is associated with two visual formats, corresponding to their uppercase and lowercase versions. Participants had to read aloud the names of single letters, and event-related potentials (ERPs) for six pairs of visually dissimilar upper-and lowercase letters were recorded. Assuming that the end product of processing is the same for upper-and lowercase letters sharing the same vocal response, ERPs were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…This linear effect emerged on right occipital sites around 200 ms post-stimulus onset and on left occipital sites around 300 ms. This finding is consistent with previous studies on letter perception indicating that phonological recoding starts on average around 220 ms post-stimulus onset and lasts until response selection at around 300 ms (Petit et al, 2006;Madec et al, 2012Madec et al, , 2016.…”
Section: Erps Resultssupporting
confidence: 93%
“…This linear effect emerged on right occipital sites around 200 ms post-stimulus onset and on left occipital sites around 300 ms. This finding is consistent with previous studies on letter perception indicating that phonological recoding starts on average around 220 ms post-stimulus onset and lasts until response selection at around 300 ms (Petit et al, 2006;Madec et al, 2012Madec et al, , 2016.…”
Section: Erps Resultssupporting
confidence: 93%
“…The aforementioned sample size was justified based on a review of the relevant literature. Most prior behavioral studies on letter and digit/number processing used various sample sizes, ranging from 3 to 20 individuals (Fischler, 1975; Fiset et al, 2009; Hayashi et al, 2013; James et al, 2005; Legge et al, 2001; Madec et al, 2016; Myers & Szücs, 2015; Perea et al, 2015; Rączy, Czarnecka, Zaremba, et al, 2020; Santee & Egeth, 1980, 1982b; Staller & Lappin, 1979; Wood, 1977), with the exception that only one study used a large sample, comprising 118 individuals (Mueller & Weidemannb, 2012). Prior neuroimaging studies on similar topics used sample sizes, ranging from 7 to 40 individuals (Cantlon et al, 2006; Carreiras et al, 2015; Lochya et al, 2018; Merkley et al, 2019; Park et al, 2012; Peters et al, 2015; Raij et al, 2000; Rączy, Czarnecka, Paplińska, et al, 2020; Santens et al, 2010; Shum et al, 2013; Tang et al, 2006; van Atteveldt et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Because of the lack of haptic familiarity, spatial complexity may then have been a determining factor over verbal encoding, resulting in similar performance between nonsense shapes and lower case letters, and superior performance for upper case letters due to their less complex shape which may facilitate verbal encoding. A similar hierarchy of processing letters, from spatial to a more abstract or verbal code, has been elucidated in the visual domain (Madec et al, 2016), therefore it is possible that similar processing can take place in haptics. Such sequential processing of letters was previously considered by Witelson (1974) who suggested that in haptics the letter stimuli are initially processed in a spatial way by their geometric features before the information to be converted verbally.…”
Section: Comparison Between Stimulus Typesmentioning
confidence: 95%
“…There are no previous haptic recognition memory studies of letters where response times were recorded, but studies on visual letter recognition are consistent with this finding. For example, Madec et al (2016) found that the upper case letters were named more quickly than lower case letters. Also, Arditi and Cho (2007) found that a text composed only from upper case letters was read faster than text composed entirely from lower case letters or mixed case text.…”
Section: Response Timesmentioning
confidence: 99%